Relación Entre Estilos De Vida, Bienestar Subjetivo Y Satisfacción De Pareja (2017)
Lifestyle is a topic of big relevancy in psychology since it refers to the form people takes care of their health, develope social relations and handle different aspects of the daily life. The relationship among lifestyle, welfare subjective and the couple satisfaction presents as a significant and interesting topic everytime the relationship of a couple could or not generate changes in the lifestyle of the people. The general objective of this investigation project is to identify the relationship between lifestyle, welfare subjective and the couple's relationship. Lifestyle are understood as a way of life based on identifiable patterns determined by the interaction between personal factors, the social interactions and the socio-economic. The welfare subjective: as the capability of assessment of each person to evaluate the happiness present in life from a personal perspective. Couple satisfaction: as the way in which it operates in function of the ability to solve conflicts, the time that couple dedicate to be together. It was developed as a qualitative investigation, of hermeneutic cut, using the semi-estructured interview with five heterosexual partners as data collection technique. It was found in general that there are satisfied with the relationship and also changes in lifestyles when there is stability in the couple. Similarly, it is emphasized that a one person will enjoy psycologycal welfare when there is alignment of the goals achieved and the goals proposed, keeping in this process it's affective part balanced and according to his structure of life.